2021
DOI: 10.3390/ijms22094700
|View full text |Cite
|
Sign up to set email alerts
|

Novel SCN5A p.Val1667Asp Missense Variant Segregation and Characterization in a Family with Severe Brugada Syndrome and Multiple Sudden Deaths

Abstract: Genetic testing in Brugada syndrome (BrS) is still not considered to be useful for clinical management of patients in the majority of cases, due to the current lack of understanding about the effect of specific variants. Additionally, family history of sudden death is generally not considered useful for arrhythmic risk stratification. We sought to demonstrate the usefulness of genetic testing and family history in diagnosis and risk stratification. The family history was collected for a proband who presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…HEK293 (human embryonic kidney 293) cells were cultured in a controlled environment (5% CO 2 , 37 °C) and maintained in an appropriate medium (DMEM/F12) (Euroclone, Milan, Italy) supplemented with 10% FBS, 2 mM L-Glutammine, 100 U/mL, and 100 μg/mL Pen/Strep. Wild-Type SCN5A complementary DNA (cDNA) was subcloned into the pcDNA3.1 plasmid, as previously described [ 49 ]. SCN5A was transiently transfected using Viafect reagent (Promega, Madison, WI, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293 (human embryonic kidney 293) cells were cultured in a controlled environment (5% CO 2 , 37 °C) and maintained in an appropriate medium (DMEM/F12) (Euroclone, Milan, Italy) supplemented with 10% FBS, 2 mM L-Glutammine, 100 U/mL, and 100 μg/mL Pen/Strep. Wild-Type SCN5A complementary DNA (cDNA) was subcloned into the pcDNA3.1 plasmid, as previously described [ 49 ]. SCN5A was transiently transfected using Viafect reagent (Promega, Madison, WI, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…However, female patients with BrS with arrhythmic events exhibit higher SCN5A mutation rates, and a relationship between gender vs. age at the onset of arrhythmic events and ethnicity [131]. In the majority of patients referred for BrS genetic testing with a single SCN5A mutation (74%), this was localized to the transmembrane region of the channel [127,132].…”
Section: Scn5amentioning
confidence: 99%
“…Although it is generally agreed that variants in the SCN5A gene are involved in BrS, it is important to think of variants even within this gene as individual variants with specific effects, rather than thinking of all SCN5A variants collectively, as some may be benign, while others pathogenic ( 26 ). Along these lines, several studies have sought to understand the effect of specific SCN5A variants ( 37 , 72 80 ). It has been recently suggested that variants in the SCN5A gene may actually be prognostic, rather than diagnostic ( 35 , 38 , 39 ).…”
Section: Genetics Of Channels Implicated By Clinical Studiesmentioning
confidence: 99%